Analysis of Potential Utilization of Sarulla Geothermal Combined Cycle Residual Fluids for Direct Use in The Coffee Industry - Harefa, Jonius Christian; Hadiyanto; Harmoko, Udi (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2022)
The Geothermal Power Plant is one of the new renewable energy power plants. In Indonesia, the realization has reached 2%. Sarulla Operations Limited is the first geothermal power plant in Indonesia, located in North Tapanuli Regency, that utilizes combined cycle technology. Coffee is the leading commodity in the North Tapanuli district, with a plant area of 17,586 hectares. Coffee is dried in the traditional way (open field drying) so that it is still constrained by rain and cloudiness and can only be done during the day. The reinjection well fluid has a temperature of 103°C with a flow rate of 4978 t/h and a pressure of 6–14 Bar. This study analyses the residual fluid energy for coffee drying purposes. Energy and exergy calculations are done manually and using DWSIM software with a total of 24 data points 24 hours a day to represent the availability of dryers both day and night. The results showed that the most energy needed to raise the drying air temperature at night from 15°C to 60°C was 125.62 kW, while the lowest energy needed to raise the drying air temperature during the day from 30°C to 40°C was 27.92 kW. The results of research calculations show the energy potential for residual fluid from geothermal plants to be used for drying coffee for 24 hours, both day and night.